2010
DOI: 10.1021/np900818c
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Toxin Production in the Cyanobacterium Microcystis: Isolation of the Toxic Protease Inhibitor Cyanopeptolin 1020

Abstract: The isolation and structure of cyanopeptolin 1020 (hexanoic acid-Glu-N[-O-Thr-Arg-Ahp-Phe-N-Me-Tyr-Val-]) from a Microcystis strain is reported. Very potent picomolar trypsin inhibition (IC50 = 670 pM) and low nanomolar values against human kallikrein (4.5 nM) and factor XIa (3.9 nM) have been determined for cyanopeptolin 1020. For plasmin and chymotrypsin, low micromolar concentrations were necessary for 50% inhibition. Cyanopeptolin 1020 was found to be toxic against the freshwater crustacean Thamnocephalus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 30 publications
3
62
0
1
Order By: Relevance
“…We could demonstrate that the notorious toxic cyanobacterium Microcystis produces an additional class of toxins, the cyanopeptolins, in addition to the well-known microcystins. [26] Cyanopeptolin 1020 was shown to constitute a 'dirty' protease inhibitor with IC 50 values down to pM concentrations. [26] In addition, we have characterized new microcystin variants both from freshwater strains in Uganda and Austria, and have investigated the structural basis for toxicity.…”
Section: Sb640mentioning
confidence: 99%
See 1 more Smart Citation
“…We could demonstrate that the notorious toxic cyanobacterium Microcystis produces an additional class of toxins, the cyanopeptolins, in addition to the well-known microcystins. [26] Cyanopeptolin 1020 was shown to constitute a 'dirty' protease inhibitor with IC 50 values down to pM concentrations. [26] In addition, we have characterized new microcystin variants both from freshwater strains in Uganda and Austria, and have investigated the structural basis for toxicity.…”
Section: Sb640mentioning
confidence: 99%
“…[26] Cyanopeptolin 1020 was shown to constitute a 'dirty' protease inhibitor with IC 50 values down to pM concentrations. [26] In addition, we have characterized new microcystin variants both from freshwater strains in Uganda and Austria, and have investigated the structural basis for toxicity. [27] Natural Products for Regenerative Medicine…”
Section: Sb640mentioning
confidence: 99%
“…However, exposure to these compounds in recreational environments and drinking water may prove to be problematic for ecological and human health since the full effect of cyanobacterial peptides individually, or in mixtures, is still largely unknown. For example, it was recently discovered that cyanopeptolin-1020 displays neurotoxicity in a zebrafish model and inhibits human kallikrein and trypsin in the low pico-to nanomolar range [66,67]. The 50% lethal concentration values against fairy shrimp (Thamnocephalus platyurus) for cyanopeptolin-1020 were similar to that of MCLR .…”
Section: Miscellaneousmentioning
confidence: 96%
“…We have demonstrated that the structurally unrelated cyanopeptolin 1020 (10) is also a toxin found in Microcystis UV-006. [24] This peptide is a member of the cyanopeptolin class of natural products, featuring a hydroxypiperidone residue as a key structural motif. We have determined very potent inhibitory activity of this peptide against a series of serine proteases, and IC 50 values as low as 670 pM against trypsin have been found.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…We have determined very potent inhibitory activity of this peptide against a series of serine proteases, and IC 50 values as low as 670 pM against trypsin have been found. [24] In addition, a range of other serine proteases such as factor XIa (3.9 nM) and kallikrein (4.5 nM) are strongly inhibited by depsipeptide 10, thus rendering cyanopeptolin 1020 (10) a 'dirty' protease inhibitor. We have also determined a LC 50 value against Thamnocephalus platyurus of 8.8 mM, which is in the same range as some of the well-known microcystins.…”
Section: Acknowledgementsmentioning
confidence: 99%